Penyidikan Terhadap Pelaku Tindak Pidana Pembunuhan Dengan Pemberatan Di Polda Jateng - Budi Setiawan; Anis Mashdurohatun; Munsyarif Abdul Chalim (Jurnal Hukum Khaira Ummah, 2019)
This study entitled Investigation Against Actors Criminal Murder With Mensing At Central Java Police. The purpose of this study: 1) To analyze the implementation of the investigation of the perpetrators of murder offenses accompanied by the weighting. 2) To analyze the inhibiting factors in an effort to uncover cases of murder accompanied by a weighting. 3) To analyze the solution and explain the accountability of murder offenses accompanied by a weighting.Result of Research: a) Effort of investigator in determining place of case happening on murder crime that is through processing to case happening case. b) Constraints that occur in the efforts of the duty in determining the crime scene in murder. 1) Damage of crime scene caused by human factor, natural factor, and animal factor. 2) Lack of experience and knowledge of investigators, meaning that investigators who are in doing their duties have not been supported by knowledge of investigations and investigations such as newly appointed investigators as investigators. 3) Unavailability of facilities and infrastructure at the time of processing the crime scene, such as must advance first tool to perform fingerprints that must be brought from the Regional Police first so that such things are considered inefficient and a constraint in conducting an investigation. d). Unavailability of Data Base, meaning that when the investigator finds fingerprints at crime scene the investigator can not find the comparative fingerprint due to the absence of Data Base about the fingerprint, thus slowing the course of the investigation c) Efforts by the investigator in overcoming the constraints when determining Place Genesis Cases of murder.Keywords: Investigation, Criminal Acts, Murder With Obstacles